2016
DOI: 10.1016/j.nicl.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Beyond production: Brain responses during speech perception in adults who stutter

Abstract: Developmental stuttering is a speech disorder that disrupts the ability to produce speech fluently. While stuttering is typically diagnosed based on one's behavior during speech production, some models suggest that it involves more central representations of language, and thus may affect language perception as well. Here we tested the hypothesis that developmental stuttering implicates neural systems involved in language perception, in a task that manipulates comprehensibility without an overt speech productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 99 publications
(182 reference statements)
1
11
0
Order By: Relevance
“…It seems possible that even lower noise levels might be sufficient to induce motor activity in PWS, especially in light of observed differences in auditory processing that may alter auditory-motor interactions (Hampton and Weber-Fox, 2008;Kikuchi et al, 2011;Mock et al, 2015;Kikuchi et al, 2017). Referencing other developmentally disordered populations (e.g., autism and dyslexia), Halag-Milo et al (2016) address this possibility in a cautionary note following a recent fMRI speech perception study in PWS. Clues to how motor systems in PWS might be impacted by white noise come from studies demonstrating enhancement of fluency under masking (Andrews et al, 1983;Martin et al, 1985;Bloodstein and Ratner, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems possible that even lower noise levels might be sufficient to induce motor activity in PWS, especially in light of observed differences in auditory processing that may alter auditory-motor interactions (Hampton and Weber-Fox, 2008;Kikuchi et al, 2011;Mock et al, 2015;Kikuchi et al, 2017). Referencing other developmentally disordered populations (e.g., autism and dyslexia), Halag-Milo et al (2016) address this possibility in a cautionary note following a recent fMRI speech perception study in PWS. Clues to how motor systems in PWS might be impacted by white noise come from studies demonstrating enhancement of fluency under masking (Andrews et al, 1983;Martin et al, 1985;Bloodstein and Ratner, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These include evidence that PWS rely more heavily on the right hemisphere for speech processing (Weber-Fox et al, 2004;Liotti et al, 2010; Robb et al, 2013;Halag-Milo et al, 2016) and exhibit differences in left hemisphere activity patterns for complex speech processing but not for simple tone processing (Biermann-Ruben et al, 2005;Corbera et al, 2005). ERP responses to speech stimuli in adults (Beal et al, 2010) and children (Beal et al, 2011;Jansson-Verkasalo et al, 2014) who stutter also suggest evidence of auditory-motor integration deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this study showed that activity in the 15 ACC was negatively correlated with the severity of stuttering symptoms, possibly reflecting a 16 failure to recruit conflict related regions to resolve stuttering (Liu et al, 2014). 17 Even though almost no studies examined functional brain activation in children who 18 stutter, some hypotheses can be derived from studies that related stuttering in children to showing less inhibitory control in CWS (Eggers et al, 2009(Eggers et al, , 2010(Eggers et al, , 2013 time, they were shown a feedback screen with the marble at the point at which they had 14 stopped it. These trials measured stimulus-driven action and were called Green-Go trials.…”
mentioning
confidence: 82%
“…Differences in brain activity patterns between AWS and adults who do not stutter can also be observed in speech perception tasks with both auditory and visual linguistic stimuli (Biermann-Ruben, Salmelin, & Schnitzler, 2005;Cuadrado & Weber-Fox, 2003;Halag-Milo et al, 2016;Weber-Fox, 2001, Weber-Fox & Hampton, 2008WeberFox et al, 2004). Using magnetoencephalography, BiermannRuben et al (2005) observed differences in brain activation in the left inferior frontal and right Rolandic regions in AWS compared with fluent adults in a language perception task that required no speech production.…”
Section: Central Neural Aspects Of Stutteringmentioning
confidence: 99%